Topological analysis of low-powered 3D-TESH network - Al Faisal, Faiz; Rahman, M.M. Hafizur; Inoguchi, Yasushi (The Institute of Electronics, Information and Communication Engineers (IEICE), 2016)
3D-TESH is a hierarchical interconnection network of multiple basic modules, where each basic module is similar to 3D-mesh network that are hierarchically interconnected for higher-level networks following the 2D-Torus connections. The static network performance and power analysis of 3D-TESH network have already been studied earlier and shown to be good than that of other networks. 3D-TESH network has achieved about 52.08% better diameter performance and near about 45.71% better average distance performance than the 3D-Torus network and even from the mathematical analysis 3D-TESH requires less than 72.73% power usage than the 5D-Torus network. In this paper, we evaluate the other important static parameters like- Packing Density, Message Traffic density, fault tolerance and etc.; and also compare the result with the other networks. We found that 3D-TESH yields much better performance than that others like- 3D Mesh, 2D Mesh, 2D Torus, TESH and even the 3D Torus networks.